Evaluasi Program Upreskilling Guru Kejuruan Berstandar Industri Bbppmpv Bisnis Dan Pariwisata - Riani, Aqsya; Retnowati, Rita; Wulandari, Dian (JURNAL MANAJEMEN PENDIDIKAN, 2024)
EVALUATION OF THE VOCATIONAL TEACHER UPSKILLING PROGRAM ACCORDING TO THE BBPMPPV INDUSTRY STANDARDS BUSINESS AND TOURISM Abstract. Teachers are an important part of education that helps prepare students for success in their field. Professional teachers must understand teaching models that suit the needs, technological changes, trends, and future projections. To achieve this, education is needed to improve the skills and knowledge of SMK teachers. The Upskilling and Reskilling Program for Industry-Standard Vocational Teachers at BBPPMPV Business and Tourism is one of the priority programs of the Directorate of Partnership and Alignment with Business and Industry, Directorate General of Vocational Education, Ministry of Education and Culture, Research and Technology. This study aims to evaluate and describe the Upskilling and Reskilling Program for industry-standard SMK teachers at BBPPMPV business and tourism in terms of context, input, process, and product (CIPP) components. This research uses qualitative methods. The data collection techniques used are interviews, observations, and documentation studies. Based on the available data and information, the results show that program planning is good. Some of the program planning is good, but some are sufficient to meet the criteria, implementation, and implementation. The program partially meets the criteria. But other aspects are quite good. The Context component requires program development, the Input component requires review and improvement as a refinement for the improvement of program components, Process and Product require review, review and improvement as an improvement and refinement of the program.